Análise do processo formativo de professores para a educação não formal realizada em organizações não governamentais - Perez, Deivis [UNESP] (My University, 2013)
This article presents research academic-scientific aimed to examine the definition and theoretical approach or model curriculum that organizes and guides the training of teachers to work in the field of non-formal education made in non-governmental organizations (NGOs). We chose to adopt the perspective of qualitative research was conducted and the case study course called Teacher Training for NGOs, developed by an NGO based in the city of São Paulo. The research instruments were used: document analysis course, semi-directive interviews with their trainers and coordinator and literature review. Examined in the course curriculum is defined as a path to be followed by students and instructors and as organizer of the subjects studied. Adopts the approach named Integrated Curriculum, in which teaching occurs through the study of problem situations and integration projects of learning. At the end of the study, it is suggested that the improvement of the course and follow information that, hopefully, support the production of further comparative research.

Este artigo apresenta pesquisa acadêmico-científica cujo objetivo foi analisar a definição teórica e a abordagem ou modelo de currículo que organiza e norteia a formação de professores para o trabalho no campo da educação não formal realizada em organizações não governamentais (Ongs). Optou-se por adotar a perspectiva qualitativa de pesquisa e foi realizado o estudo de caso do curso denominado Formação de Professores para Ongs, desenvolvido por uma Ong sediada na cidade de São Paulo. Os instrumentos de pesquisa utilizados foram: análise dos documentos do curso, entrevistas semidiretivas com os seus formadores e coordenador e revisão da literatura. No curso examinado define-se currículo como caminho a ser percorrido por alunos e formadores e como organizador das temáticas estudadas. Adota-se a abordagem nomeada Currículo Integrado, em que o ensino ocorre por meio do estudo de situações-problema e projetos integradores das aprendizagens. Ao final da pesquisa, sugere-se o aperfeiçoamento do curso e seguem informações que, espera-se, apoiem a produção ulterior de pesquisas comparativas.
Analysis of a formation process of teachers for non-formal education made in non-governmental organizations
Keywords: Curriculum; Teacher training; Non-formal education; Currículo; Formação de professores; Educação não formal